4‐1BB and cytokines trigger human NK, γδ T, and CD8+ T cell proliferation and activation, but are not required for their effector functions. Issue 1 (15th December 2022) - Vidard, Laurent
Abstract: Introduction: This study was designed to compare the costimulatory molecules and cytokines required to trigger the proliferation and activation of natural killer (NK), γδ T, and CD8 + T cells, and gain in‐depth insight into the mechanisms shifting tolerance to immunity. Methods: K562‐derived artificial antigen‐presenting cells (aAPCs); that is, K562 forced to express CD86 and 4‐1BBL costimulatory receptors, in the presence of cytokines, were used to mimic dendritic cells (DCs) and provide signals to support the proliferation and activation of NK, γδ T, and CD8 + T cells. Results: Three signals are required to trigger optimal proliferation in MART‐1‐specific CD8 + T cells: activation of T‐cell receptors (TCRs) by the major histocompatibility complex (MHC) I/peptide complexes (signal 1); 4‐1BB engagement (signal 2); and IL‐15 and IL‐21 receptor co‐signaling (signal 3). NK and γδ T cell proliferation also require three signals, but the precise nature of signal 1 involving cell‐to‐cell contact was not determined. Once they become effectors, only signal 1 determines the sensitivity or resistance of the target cells to cytolysis by killer lymphocytes. When freshly purified, none had effector functions, except the NK cells, which could be activated by CD16 engagement. Conclusions: Therefore, lymphocytes committed to kill are produced as inactive precursors, and the license to kill is delivered by three signals, allowing for extensive proliferation and effector function acquisition. This data challenges the paradigm of anergy and supports the danger signal theory originally proposed by Polly Matzinger, which states that killer cells are tolerant by default, thereby protecting the mammalian body from autoimmunity. Abstract : Three signals are required to trigger primary NK, gamma/delta T, and CD8 + T cell proliferation and activation. When freshly purified, none had effector functions, except the NK cells, which could be activated by CD16 engagement. Therefore, lymphocytes committed to kill are produced as inactive precursors, and the license to kill is delivered by three signals, allowing for extensive proliferation and effector function acquisition.